Russian Journalists and the 'Great Patriotic War of the Soviet Union'. Issue 3 (2nd October 2022) - Johnson, Owen V.; Mammadov, Rashad
ABSTRACT: This article focuses on the role of Russian journalists and their reporting during World War II. We argue that, generally, the historical trajectory of journalism and the press in Russia significantly diverges from the often-cited 'norm' of the West. We look at the press in the Great Patriotic War but recognize that it cannot be judged based on Western-centric institutional culture. We conclude that professionalism in Soviet eyes meant something significantly different from its equivalent in Western journalism, and this divide was even more pronounced during World War II. Nevertheless, the Soviet press became a powerful tool on the road to victory.